2018
DOI: 10.1186/s13568-018-0611-6
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of neutral protease from Aspergillus oryzae Y1 isolated from naturally fermented broad beans

Abstract: The strain Y1, with a notably high production of neutral protease, was isolated from naturally fermented broad beans and subsequently identified as Aspergillus oryzae, through the analysis of its morphology characteristics and 18S rDNA sequence. Naturally fermented broad beans are the main raw material in Sichuan broad-bean sauce. The neutral protease from Aspergillus oryzae Y1 was purified using ammonium sulphate precipitation and DEAE-Sepharose Fast Flow chromatography, which resulted in a 10.0-fold increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 42 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Similar to the present study, aspartic proteases purified from A. oryzae BCRC 30118 (Yin, Chou, and Shann-Tzong Jiang 2013) and Phanerochaete chrysosporium (Rodrigues et al 2017) showed high enzyme activity with a specific activity of about 117.62 U/mg and 224.7 U/mg, respectively. The purification fold of 10.0 (Ao et al, 2018) and 9.0 (Fazouane-Naimi et al 2010) gained for the neutral protease from A. oryzae Y1 after DEAE-Sepharose Fast Flow chromatography and for aspartic protease enzyme from A. niger FFB1after gel filtration was comparable with the present study. However, the specific activity of 1.2 U/mg (Nouani et al, 2011) and (248.1 U/g) (Souza et al 2017) obtained for an aspartic protease from M. pusillus and A. foetidus, respectively after gel filtration were smaller than this study.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the present study, aspartic proteases purified from A. oryzae BCRC 30118 (Yin, Chou, and Shann-Tzong Jiang 2013) and Phanerochaete chrysosporium (Rodrigues et al 2017) showed high enzyme activity with a specific activity of about 117.62 U/mg and 224.7 U/mg, respectively. The purification fold of 10.0 (Ao et al, 2018) and 9.0 (Fazouane-Naimi et al 2010) gained for the neutral protease from A. oryzae Y1 after DEAE-Sepharose Fast Flow chromatography and for aspartic protease enzyme from A. niger FFB1after gel filtration was comparable with the present study. However, the specific activity of 1.2 U/mg (Nouani et al, 2011) and (248.1 U/g) (Souza et al 2017) obtained for an aspartic protease from M. pusillus and A. foetidus, respectively after gel filtration were smaller than this study.…”
Section: Discussionsupporting
confidence: 87%
“…They reported anti-bacterial peptide production in the fish viscera hydrolysate. Ao et al ( 2018 ) undertook the characterization of neutral protease from Aspergillus oryzae Y1 isolated from naturally fermented broad beans and reported it to be a 45 kD protein with 7.0 optimum pH and 55 °C optimum temperature. De Oliveira et al ( 2020 ) reported about production of a relatively thermostable protease by the fungus Moorella speciosa , with 6.5 as the optimum pH.…”
Section: Neutral Proteasesmentioning
confidence: 99%
“…Furthermore, B3 and B5 appeared on the same branch as Staphylococcus gallinarum and Enterobacter hormaeche , respectively, exhibiting the closest relationship (Figure 3 ). A. oryzae is recognized as safe and used in fermented condiments, such as Chinese and Japanese soy sauce, for thousands of years (Ao et al., 2018 ; Kim, Lim, et al, 2017 ; Zhao et al., 2019 ), which can secrete a large amount of protease and carbohydrate hydrolase to decompose the raw materials into short peptides, amino acids, oligosaccharides, and other flavor substances. Studies have shown that the secretion of more A. oryzae enzymes is regarded as a basal factor affecting the quality of fermented soybean paste (Yoshino et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%